Evaluating the effect of IP and IGP on the ICMP throughput of a WAN - Khan , Burhan ul Islam; Dar , Humaira; Shah, Asadullah; Olanrewaju, Rashidah Funke (Design for Scientific Renaissance, 2013)
Routing can rightly be regarded as the heartbeat of any WAN (Wide Area Network) setup; and same holds true when it comes to internet. Routing has a direct influence on the speed of internet surfing. Today the world is witnessing the steady switch of Internet from IPv4 to IPv6. The main goal addressed in this paper is to evaluate the effect of different combinations of Interior Gateway Protocol and Internet Protocol on the ICMP (Internet Control Message Protocol) based throughput of a WAN. Results are fetched by simulating WANs on Packet Tracer and a 22 experimental design technique has been employed for analysing results and drawing conclusions.